1999
DOI: 10.1002/(sici)1099-0518(19990815)37:16<3309::aid-pola29>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydroperoxide formation in irradiated polyethylene

Abstract: Spectroscopic analysis for hydroperoxide in irradiated ultrahigh molecular weight polyethylene, on the basis of the formation of a nitrate derivative after exposure to dilute nitric oxide, is examined. Hydroperoxide is found to be an important intermediate in the oxidation of polyethylene and is believed to result from hydrogen abstraction reactions by peroxy radicals in a polyethylene matrix. During γ irradiation in air, the rates of bimolecular combination of peroxy radicals on the surface to form ketones or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…9) with the oxygen diffusion–control oxidation process cannot adequately explain the subsurface oxidation and its location beneath the surface in the shelf‐aged or clinically retrieved UHMW polyethylene that historically has been gamma sterilized in air. In a concurrent study,35 we found that following irradiation the hydroperoxide concentration at the surface of air‐irradiated specimens first increased (within 3 months) and then slowly decreased with storage time in ambient air (up to 21 months). In contrast, the hydroperoxide below the surface increased with storage time and showed a faster increase than on the surface.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…9) with the oxygen diffusion–control oxidation process cannot adequately explain the subsurface oxidation and its location beneath the surface in the shelf‐aged or clinically retrieved UHMW polyethylene that historically has been gamma sterilized in air. In a concurrent study,35 we found that following irradiation the hydroperoxide concentration at the surface of air‐irradiated specimens first increased (within 3 months) and then slowly decreased with storage time in ambient air (up to 21 months). In contrast, the hydroperoxide below the surface increased with storage time and showed a faster increase than on the surface.…”
Section: Discussionmentioning
confidence: 79%
“…That is, the concentration of residual free radicals is at its minimum at the surface, gradually increasing below the surface and reaching a plateau at about 1 mm below the surface. Residual free radicals that remain after irradiation react with oxygen that diffuses in during storage in air and form peroxy radicals, which either can combine with each other to form ketones, or can abstract hydrogen atoms from polyethylene to form hydroperoxides 35, 37…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most important N1s component appears at a BE of 402.3 eV which is between oximes (C N-OH, BE = 400.5 eV [22,23] ) and nitroso groups (C-N O, BE = 403.7 eV). Consequently, the nitrogen group of interest has one bond to oxygen and at least one bond to a carbon atom with one or more bonds to oxygen.…”
Section: Radicalsmentioning
confidence: 99%